Epidemiology of work-related diseases and accidents : tenth report of the Joint ILO/WHO Committee on Occupational Health, meeting held in Geneva from 1 to 7 September 1987 - World Health Organization; International Labour Organization (ILO) Committee on Occupational Health (Geneva : World Health Organization, 1989)
Assesses the ways in which epidemiological research can be used to determine when factors in the workplace operate as causes of disease or accidents. Addressed to occupational safety and health personnel, the book serves as both a detailed guide to the application of different epidemiological methods and a review of what these methods have already contributed to knowledge about health risks in the work environment and methods of prevention. In view of the complexity of human and environmental factors that need to be elucidated, the book gives particular attention to questions of study design and methodology that can strengthen the capacity of epidemiolgical research to yield sensitive, specific, and reliable data. The first main chapter, devoted to work-related diseases, concentrates on chronic nonspecific respiratory disease, cardiovascular disease, and musculo-skeletal disorders, including low-back pain, neck and upper limb disorders, and osteo-arthrosis. These common disorders, which were selected because of their complex multifactorial etiology, are used to illustrate specific problems inherent in epidemiological research aimed at identifying and quantifying the etiology of work-related disorders. Readers are given a formula for computing the strength of a given etiological factor, advice on the selection of indicators and measures of exposure, and a comparison of the appropriateness of different methodological approaches and study designs for providing evidence for or against the causality of an observed association. Data indicating the work-relatedness of each of these disorders are also succinctly reviewed. Work-related accidents are covered in the second half of the book, which reminds readers that an estimated 180,000 deaths and 110 million injuries are attributed each year to accidents at the workplace. An outline of present recording systems and problems with the statistical collection of data is followed by a detailed discussion of the uses of epidemiology to focus attention on dangerous trades, occupations, or tasks, to identify the causes of accidents within particular occupational environments, and to test the effectiveness of preventive methods. Details range from criteria for reporting near-accidents and dangerous occurrences to features of plant design and operation associated with superior safety performance.
Keywords: Epidemiology of work-related diseases and accidents